(untitled) (Dhaka University Journal of Biological Sciences, 2016)
In the present investigation, Station 5 located in the downstream of the Merbok estuary showed higher density of zooplankton (132 × 103 ind/m3) but it was lowest (83 × 103 ind/m3) was at Station 2 (upstream). The highest and lowest zooplankton density was observed in May and November, respectively. Twenty groups of zooplankton were recorded and copepod was the dominant group at all sampling stations during the sampling period. Months and stations were statistically significant (Kruskal-Wallis H test; p < 0.05) factors that affect the density of zooplankton, temperature, salinity and nutrients. Mann-Whitney U test showed that temperature, NO2 and zooplankton density were significantly different between seasons (p < 0.01). Significant correlation among zooplankton density, chl a concentration and nutrients (p < 0?01) were observed. Dhaka Univ. J. Biol. Sci. 25(1): 47-55, 2016